Induction of cognitive impairment by scopolamine and noncholinergic agents in rhesus monkeys. - Rupniak, N; Samson, N; Steventon, M; Iversen, S (1991)
In primates, treatment with scopolamine impairs performance of a spatial delayed response task in a way which mimics deficits seen spontaneously in aged primates and demented patients. Despite their efficacy in reversing scopolamine induced disruption, the effects of cholinergic agonists on cognition in aged primates and dements are unimpressive, suggesting that other neurotransmitter systems are also involved in this type of deficit. We have induced a scopolamine-like impairment of spatial delayed response performance in rhesus monkeys using phencyclidine (0.1-0.2 mg/kg i.m.), lorazepam (0.4-0.6 mg/kg s.c.) or tetrahydrocannabinol (1-4 mg/kg p.o.), but not amphetamine (0.1-0.4 mg/kg i.m.), yohimbine (0.1-1.0 mg/kg i.m.) or morphine (2-4 mg/kg i.m.). Our findings suggest that disruption of specific neurotransmitter systems other than acetylcholine may contribute importantly to cognitive decline in aging and dementia.